PEDAGOGICAL ESSENCE OF THE COMPETENCY-BASED APPROACH AND ITS ROLE IN MUSIC EDUCATION - Omonova Fayziniso Anvar qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  article  examines  the  pedagogical  essence  of  the  competency-based approach, its didactic potential in music education, and its role in learning outcomes assessment (competency-based assessment). The research design employs comparative analysis of regulatory and legal documents (Uzbekistan’s State Educational Standards and higher education standards), scholarly literature, and international experience. The results show that the competency-based approach in music education strengthens an outcome-oriented model focused not merely on  “knowledge,” but on performance-based  activity,  creative  products,  reflection,  and  digital  pedagogy.  Teacher competencies are shown to be systematically developed through TPACK and digital competence  frameworks.  Although  the  competency-based  paradigm  is  being consolidated in Uzbekistan through state educational standards, several “gaps” remain in  music  education,  particularly  in  assessment  criteria,  integration  of  digital competence,  and  methodological  support  for  teachers.  Based  on  international experience, the discussion proposes a “music education competency matrix” adapted to the Uzbek context, along with a rubric-based assessment model.